Evaluasi Manfaat Sekolah Lapang Pengendalian Hama Terpadu (SLPHT) Perkebunan Kopi Rakyat dalam Meningkatkan Pendapatan Petani - Hendiarto Hendiarto (Jurnal Perlindungan Tanaman Indonesia, 2007)
Integrated pest management (IPM) Farmers Field School (FFS) on coffee crop had been conducted in East Java since 1998 until 2003. The IPM-FFS program aimed to increase productivity and quality of the coffee bean through the improvement of the crop and the environment. The aim of this paper was to 1) describe the benefit of the implementation of IPM practicing farmers. The tabulation descriptive method, the profit function and logit function analysis were used. Results showed that the application of IPM technology could increase the profit and the quality of the coffee bean and the price of coffee at farmer level obviously affected the farmer to adopt IPM and increase the income of the farming.